2017
DOI: 10.1063/1.4978312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on Raman spectra of monolayer graphene samples gradually disordered by ion irradiation

Abstract: The Raman scattering spectra (RS) of two series of monolayer graphene samples irradiated with various doses of C + and Xe + ions were measured after annealing in high vacuum, and in forming gas (95%Ar+5%H2). It was found that these methods of annealing have dramatically different influence on the RS lines. Annealing in vacuum below 500 • C leads to significant decrease of both D-line, associated with defects, and 2D-line, associated with the intact lattice structure, which can be explained by annealing-induced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Extended research has been reported in literature in relation to Raman studies of graphene and GO (Dresselhaus et al, 2008;Ferrari and Basko, 2013;Bokobza et al, 2014). Especially with regards to the annealing process of the GO, numerous studies have evaluated the effects of the temperature and the annealing environment both for mechanically exfoliated and CVD grown graphene (Lin et al, 2012;Botcha et al, 2014;Alyobi et al, 2017;Zion et al, 2017). Xueshen et al (2013) have studied the effects of thermal annealing in monolayer graphene obtained by mechanical exfoliation with scotch tapes.…”
Section: Introductionmentioning
confidence: 99%
“…Extended research has been reported in literature in relation to Raman studies of graphene and GO (Dresselhaus et al, 2008;Ferrari and Basko, 2013;Bokobza et al, 2014). Especially with regards to the annealing process of the GO, numerous studies have evaluated the effects of the temperature and the annealing environment both for mechanically exfoliated and CVD grown graphene (Lin et al, 2012;Botcha et al, 2014;Alyobi et al, 2017;Zion et al, 2017). Xueshen et al (2013) have studied the effects of thermal annealing in monolayer graphene obtained by mechanical exfoliation with scotch tapes.…”
Section: Introductionmentioning
confidence: 99%
“…Highly oriented pyrolytic graphite (HOPG), which is produced by pyrolysis of a carbonaceous gas at high temperature, is considered defect‐free, but defects can be created on the surface of HOPG by sputtering the surface with an ion beam . Studies have shown that defects on graphite and graphene surfaces can be repaired under a carbon atmosphere, a noble gas atmosphere, or in the vacuum . The repairs can improve their thermal and electrical conductivities and enhance their mechanical strength .…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies have shown that defects on graphite and graphene surfaces can be repaired under a carbon atmosphere, a noble gas atmosphere, or in the vacuum. [11][12][13][14][15][16][17][18][19] The repairs can improve their thermal and electrical conductivities and enhance their mechanical strength. 7,12 Cheng's group reported using an O 2 plasma to sputter the surface of HOPG at 90°C and then increased the sizes of the resulting defects to 10 to 20 nm with an H 2 plasma at 525°C.…”
mentioning
confidence: 99%
“…For C + ions with M = 12 in atomic mass units (amu) and for Xe + ions (M = 131 amu) with E = 35 keV, k = 0.06-0.08 and 0.8 correspondingly [10]. The changes in the intensities of both D-and 2D-lines ID and I2D with increase of Nd in these samples were studied in [10][11][12]. It was shown that I2D continuously decreases, while ID first increases and then decreases, the maximal value is achieved at Nd ≈ 4x10 12 cm -2 , which corresponds to the mean distance between defects Ld ≈ (Nd) -1/2 ≈ 5 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Ion irradiation induced disorder is not quite stable: some changes in the intensity of RS line were observed in irradiated samples after the long-term ageing (about one year) [10]. It was shown also that high-temperature annealing of radiation damage in vacuum and in the forming gas leads to partial reconstruction of the intensity of RS lines and lattice structure [11].…”
Section: Introductionmentioning
confidence: 99%